Healthy food diversity and the risk of major chronic diseases in the EPIC-Potsdam study - Daniela V. Nickel; Franziska Jannasch; Elif Inan-Eroglu; Olga Kuxhaus; Matthias B. Schulze (Scientific Reports)
Abstract Practicing a diverse diet may reduce chronic disease risk, but clear evidence is scarce and previous diet diversity measures rarely captured diet quality. We investigated the effect of the Healthy Food Diversity (HFD)-Index on incident type 2 diabetes (T2D), myocardial infarction (MI) and stroke among a middle-aged German population. The EPIC-Potsdam study recruited 27,548 participants from 1994 to 1998. Semiquantitative food frequency questionnaire was used to calculate the HFD-Index. Longitudinal associations of HFD-Index and verified incident diseases were investigated by multiple-adjusted Cox proportional hazards regression models. Among 26,591 participants (mean age 50.5 years, 60% women), 1537, 376 and 412 developed T2D, MI and stroke, respectively, over an average follow-up of 10.6 years. There was no association between HFD-Index and incident T2D or MI. Higher compared to lower HFD-Index was inversely associated with incident stroke in men [HR (95% CI): 0.80 (0.70, 0.92)], but positively associated with incident stroke in women [1.20 (1.01, 1.42)]. Although there was no clear association between HFD-Index and T2D or MI incidence, we found a beneficial association in men and a harmful association in women for incident stroke. We emphasised the need for further investigations on combining diet diversity and diet quality in relation to health outcomes.